THE CORRELATION OF SOCIAL ENVIRONMENT TOWARD CHILDREN'S LEARNING ACHIEVEMENT AT SMA PGRI KUPANG - Riani Nomleni (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2023)
This study specifically looked at how the social environment affects student achievement at SMA PGRI Kupang. The objective of this study was to explain the relationship between social environment and learning achievement at SMA PGRI Kupang. An ex post facto quantitative method was used to examine the relationship between social environment and children's learning achievement. The data were collected using a form of questionnaires and documentation through 14 students (XI IPS) as samples. The data was analyzed using some techniques, including; descriptive statistical analysis, mean analysis, average value analysis, and correlation analysis to test the hypothesis. The product-moment correlation test was a statistical analysis technique. This study found a strong link between children's learning achievement and their social environment. One of the factors of success was determined by the social environment. As a result, SMA PGRI Kupang had a bad environment that can affect learning activities and lower children's learning achievement. Based on the data analysis, 0.73 at a 5% significance level, and rtable score was 0.24. This means that the value is greater than the rtable value, with 0.73 greater than 0.24. The first hypothesis (Ho) was accepted, while the alternative hypothesis (Ha) was rejected.